Obstructive sleep disordered breathing in 2-to 18-year-old children: diagnosis and management - (:unkn) unknown (EUROPEAN RESPIRATORY SOC JOURNALS LTD, 2016)
This document summarises the conclusions of a European Respiratory Society Task Force on the diagnosis and management of obstructive sleep disordered breathing (SDB) in childhood and refers to children aged 2-18 years. Prospective cohort studies describing the natural history of SDB or randomised, double-blind, placebo-controlled trials regarding its management are scarce. Selected evidence (362 articles) can be consolidated into seven management steps. SDB is suspected when symptoms or abnormalities related to upper airway obstruction are present (step 1). Central nervous or cardiovascular system morbidity, growth failure or enuresis and predictors of SDB persistence in the long-term are recognised (steps 2 and 3), and SDB severity is determined objectively preferably using polysomnography (step 4). Children with an apnoea-hypopnoea index (AHI) >5 episodes.h(-1), those with an AHI of 1-5 episodes.h(-1) and the presence of morbidity or factors predicting SDB persistence, and children with complex conditions (e.g. Down syndrome and Prader-Willi syndrome) all appear to benefit from treatment (step 5). Treatment interventions are usually implemented in a stepwise fashion addressing all abnormalities that predispose to SDB (step 6) with re-evaluation after each intervention to detect residual disease and to determine the need for additional treatment (step 7).
Keywords: POSITIVE AIRWAY PRESSURE; QUALITY-OF-LIFE; PRADER-WILLI-SYNDROME; RAPID MAXILLARY EXPANSION; AMBULATORY BLOOD-PRESSURE; THE TUCSON CHILDRENS; POLYGRAPHIC RESPIRATORY EVENTS; DEFICIT HYPERACTIVITY DISORDER; LEUKOTRIENE MODIFIER THERAPY; EXCESSIVE DAYTIME SLEEPINESS